2015
DOI: 10.1002/mc.22297
|View full text |Cite
|
Sign up to set email alerts
|

Loss of GDF10/BMP3b as a prognostic marker collaborates with TGFBR3 to enhance chemotherapy resistance and epithelial-mesenchymal transition in oral squamous cell carcinoma

Abstract: Growth differentiation factor-10 (GDF10), commonly referred as BMP3b, is a member of the transforming growth factor-β (TGF-β) superfamily. GDF10/BMP3b has been considered as a tumor suppressor, however, little is known about the molecular mechanism of its roles in tumor suppression in oral cancer. Clinical significance of GDF10 downregulation in oral squamous cell carcinoma (OSCC) was evaluated using three independent cohorts of OSCC patients. The molecular mechanisms of GDF10 in the suppression of cell surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 54 publications
2
21
0
Order By: Relevance
“…The clinicopathological characteristics in 154 patients are shown in Table S4 . The multivariate Cox analysis showed that cigarette smoking, differentiation, and lymph node metastasis are independent risk factors to predict poor outcome of OSCC patients (Table S5 ), which is similar to our recent study on OSCC 41 . Subsequently, our results indicated that the expression of Cdc7 is significantly positively correlated with HCLK2 ( P = 0.001) and ATR ( P = 0.037); it has the same trend with the expression of HSP90 (Fig.…”
Section: Resultssupporting
confidence: 87%
“…The clinicopathological characteristics in 154 patients are shown in Table S4 . The multivariate Cox analysis showed that cigarette smoking, differentiation, and lymph node metastasis are independent risk factors to predict poor outcome of OSCC patients (Table S5 ), which is similar to our recent study on OSCC 41 . Subsequently, our results indicated that the expression of Cdc7 is significantly positively correlated with HCLK2 ( P = 0.001) and ATR ( P = 0.037); it has the same trend with the expression of HSP90 (Fig.…”
Section: Resultssupporting
confidence: 87%
“…We conducted RNA-Seq analysis to identify differentially expressed genes (DEGs) between clinical TNBC specimens and tumor-matched controls and found significant downregulation of growth differentiation factor-10 (GDF10), a member of the transforming growth factor-β (TGF-β) superfamily [12]. GDF10 plays an important role in cell proliferation and differentiation and is also known as BMP-3B due to its close relationship with bone morphogenetic protein-3 (BMP3), another member of the TGF-β superfamily [12]. TGF-β signals through three cell surface receptors, namely TGFBR1/2/3 [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that increased levels of Ly6A/E (Sca-1) promote breast tumorigenesis via disruption of TGF-β signaling and suppression of GDF10 expression in mouse models [ 2 ]. GDF10 has been shown to regulate epithelial to mesenchymal transition, growth and invasion in oral squamous cell carcinoma [ 16 ]. These finding suggest that Ly6 genes family members have important role multiple cancer but a comprehensive analysis of multiple members of Ly6 gene family and its relation to cancer patient survival is lacking.…”
Section: Introductionmentioning
confidence: 99%